The Meaning of Javanese Slametan Arwah in The Perspective of Eucharistic Theology Through Umberto Eco’s Sign of Production Theory - Manggala, Jakobus Aditya Christie; Nugroho, Isodorus Bangkit Susetyo Adi (Asosiasi Ahli Filsafat Keilahian Indonesia, 2024)
Death is a universal experience that brings profound grief to the surrounding family and community. While the journey of grieving is deeply personal—shaped by each individual’s unique relationship with the deceased—cultural factors play a significant role in how humans derive meaning from death and navigate the accompanying grief. In a context in which culture and Catholicism are interwoven, like the case in the Javanese Catholic community, it is not uncommon that there would arise questions on meaning and confusion on the rites associated with death. This research discusses the resonance and dissonance between the slametan arwah rite in Javanese culture and the rite to commemorate the deceased in the Eucharistic celebration. Utilizing the framework of 'mode of sign production' by Umberto Eco, this study shows that slametan arwah rituals share some similarities with the Eucharist: in them, the centrality of communion expressed and strengthened through prayer and shared meals, the remembrance of the deceased as a way of maintaining harmony between the deceased with the living, and the ceremonial structure both practices hold. However, the critical point to observe is that there are distinctions between them in their perspectives on salvation, the presence of death remembrance is not central within the Eucharist, and an understanding of Christ's sacrificial offering in the Eucharist. This study is organized into four sections based on Umberto Eco's Semiotics of Signs: Recognition, Ostentation, Replica, and Invention. Before these analyses, an overview of the slametan arwah rite within the Javanese worldview will be provided. Through these discussions, the study aims to help Catholic Javanese deepen their understanding of both practices to prevent theological confusion. It also aims to contribute to the vision of inculturation advocated by Vatican II, fostering a richer integration of local customs with church theology.